Pharmacognostic and traditional properties of Cissus quadrancularis Linn -An overview - S.Justin Raj; Baby joseph (International Journal of Pharma and Bio Sciences, 2010)
Cissus quadrangularis, a medicinal plant indigenous to Asia and Africa. It is used in indigenious system of medicine like ayurveda, siddha, unani and homoeopathy. The active compounds isolated form this plant are considered to be very effective in various treatments, such as osteoporosis, asthma, cough, hemorrhoids, and gonorrhea. The paper reports on its traditional, phytochemical and pharmacognostic properties such as antioxidant, anticancer, analgesic, anti-inflammatory and antipyretic activities of Cissus quadrangularis.